Of dreams and llaves; All in the game; Tropical Depression - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Documents the jai-alai issue; the scalpers; and the band composed of Filipino famous for its Reggae music.
Of dreams and llaves (15 min.) -- All in the game (15 min.) -- Tropical Depression (15 min.)
VHS.
Reporter, Marga Ortegas.
Keywords: Jai-alai -- Philippines; Band musicians -- Philippines; Ticket brokerage -- Philippines